Infection of Cypriniform Fishes with Argulus coregoni (Crustacea: Branchiura: Argulidae) in a Low-elevation Stream, Central Japan - Kazuya Nagasawa; Hiroyuki Nishimura (Species Diversity)
Recent studies have reported that salmonids and ayu Plecoglossus altivelis altivelis (Temminck and Schlegel, 1846), both of which are salmoniform fishes, serve as important hosts for Argulus coregoni Thorell, 1864. These studies found the parasite in the upper and middle-lower reaches of large rivers, respectively, originating from high-elevation mountain areas in central Japan. However, very recently, we collected specimens of A. coregoni from cypriniform fishes at a low elevation (25 m) in the lower reaches of the Kushiko River, a small stream originating in a mountain area and a tributary of the Hasu River, in Fukui Prefecture, central Japan. The lower Kushiko River lies in a rural area surrounded by rice fields, but its water is unpolluted and running. The infected cypriniform fishes were fat minnow Rhynchocypris lagowskii steindachneri (Sauvage, 1883) (Leuciscidae) and dark chub Nipponocypris temminckii (Temminck and Schlegel, 1846) (Xenocyprididae), and these fishes dominated at the collection site. No salmonids or ayu were collected there, and other fishes (one species of amblycipitid and one species of gobiid) were rare and uninfected. These facts indicate that, despite the fact that the river flows at low elevations, A. coregoni is able to utilize the two dominant cypriniform fishes (fat minnow and dark chub) as its hosts and maintain its population there. This is in contrast to the previous reports that A. coregoni exclusively infects salmonids and ayu in Japan. This paper reports on the occurrence of A. coregoni on the two cypriniform fishes and also describes the parasite from these fish species. Fat minnow represents a new host record for the parasite.